Isolation of food waste degrading bacteria as green agent for making compost fertilizer - Syaifudin, Andang; Hayyilana, Caesaria Rohmatul (Universitas Bung Hatta, 2024)
Food waste is one of the problems that occurs in the city of Semarang. The impact that arises from the large amount of food waste is the appearance of bad odors, causing disease and environmental pollution. One alternative used to reduce the amount of food waste is to turn it into compost. This research aims to determine the potential of bacteria isolated from food waste obtained from the canteen in degrading food waste. The medium used to culture bacteria is the synthetic medium YEMA (Yeast extract mannitol agar). The bacterial isolation process produced 10 bacterial isolates that grew on the media, then these isolates were screened with various tests to determine their ability to degrade cellulose, protein, lipids and starch. From the results of the research, data was obtained showing that the screening test obtained 4 isolates that had the highest potential, namely isolates with the codes FWD, FWH, FWI, and FWJ with the largest cellulolytic index of 1.5, the largest proteolytic index of 3.3, the largest lipolytic index of 3.3, and the amylolytic index. the largest is 1.2.